ASUPAN GIZI, POLA MAKAN DAN KESEHATAN GIGI ANAK - Agung, I Gusti Ayu Ari; Nurlitasari, Dewi Farida (Interdental: Jurnal Kedokteran Gigi, 2017)
Nutrition, diet and dental health have strong association especially for children who are in the growth and development phase. Healthy and adequate nutrition play vital role to support dental health in children. Dental caries is one of the most frequent chronic infections in children and also has significant connection with nutrition aspect. The behaviour of high sugar food and beverage intake, fast food consumption, and frequent snacks consumption between meals increase the risk of dental caries. Overweight and obesity are also can increase the risk of dental caries in children. Usage of fluoride and xylitol as the prevention of dental caries. Another important prevention steps in reducing the risk of dental caries in children include limiting intake of sugar, fast food, snacks, and soda drink. Problems dental health of children in Indonesia is still a public health problem. Deficiency of energy, protein, vitamins A, C, D, folic acid, minerals Fe, Zn, Ca, P, F cause abnormalities in the teeth. WHO have included F as one of the essential nutrients in the prevention of dental caries. Anticariogenic diet are milk and its products like cheese. Cariogenic diet are carbohydrates that can be fermented by microorganisms such as sweet foods, candy, soda and fast food.